SUCCESS FACTORS STRENGTHEN STRONG COMMUNITY LIVELIHOOD: A CASE SUDY OF BAN KROK LUEK, NAM ROP SUB-DISTRICT, LAN SAK DISTRICT, UTHAI THANI PROVINCE - Boonnuang, Anantawoot; Mhuentoei, Tanongsak; Thamma, Dennarong (Journal of MCU Nakhondhat, 2023)
This research aimed to analyze success factors conducive to strengthening the strong community livelihood of Ban Krok Luek, Nam Rop subdistrict, Lan Sak, Uthai Thani Province. Qualitative research was adopted in this study. Key informants included 25 participants involved in the community livelihood project and 2 community development officials responsible for the project. Data were collected via in-depth interviews with individual and focus-group discussions. After that, they were analyzed using content analysis to make inferences about the outcome. The result of the research revealed that three principal success factors conducive to strengthening the strong community livelihood of Ban Krok Luek, in descending order of influence, were community leader (strong leadership highly regarded within the community/the ability to disseminate knowledge together with persuasive ability to motivate community members to act willingly), participation of community members (whereby all members lived together with love, unity, cooperation, fully willing to convene, plan, contributing opinion, acting, follow-up, and make revision on plan whenever necessary), supportive networking (whereby the villagers joined as members of network partners inside and outside the community to promote and act cohesively to support the community’s activities). In addition, there were four supporting factors: household economy, socio-cultural, community capital, and support from government agencies also contributed to their success.